A molecular phylogeny of the Dactylogyridae sensu Kritsky & Boeger (1989) (Monogenea) based on the D1-D3 domains of large subunit rDNA - Simková, A; Matejusová, I; Cunningham, C O (Parasitology, 2006)
Phylogenetic analyses based on the partial large subunit rDNA (LSU) sequences of polyonchoinean monogeneans belonging to the Dactylogyridea and Monocotylidea were generated to investigate relationships among various subfamilies of the Dactylogyridae sensu Kritsky & Boeger, 1989. Monophyly of the Dactylogyridae was supported by all analyses performed. Status of the Ancyrocephalidae sensu Bychowsky & Nagibina, 1978 and Ancyrocephalinae sensu Kritsky & Boeger, 1989 was revised based on the present data. All phylogenetic analyses indicated polyphyletic origins of the Ancyrocephalidae and Ancyrocephalinae. Freshwater species of Ancyrocephalinae (Actinocleidus, Ancyrocephalus, Cleidodiscus and Urocleidus) and Ancylodiscoidinae (Thaparocleidus) collected from the fish in European waters were positioned at the base of the Dactylogyridae. The Dactylogyrinae formed a monophyletic group, sister to a clade including the Pseudodactylogyrinae and the tropical and subtropical Ancyrocephalinae. Analyses including only data set on Dactylogyridea were focused on relationships between representatives of the Asian and European Dactylogyrus species. Dactylogyrus species formed a monophyletic group, and the parasite colonization appeared to follow the dispersal history of the Cyprinidae from Asia to Europe. Three lineages of Dactylogyrus species were recognized: the first including species specific to hosts of Asian origin, the second by Dactylogyrus species from Chinese fish hosts, and the third included Dactylogyrus species from European cyprinids and one species from a percid host. The position of D. cryptomeres from Gobio gobio seems to be unresolved.
Keywords: molekulární evoluce; Molecular Sequence Data; Platyhelminths; Sequence Analysis, DNA; polymerázová řetězová reakce; Polymerase Chain Reaction; ploštěnci; DNA, Helminth; DNA, Ribosomal; Base Sequence; sekvence nukleotidů; Animals; zvířata; DNA helmintů; fylogeneze; ribozomální DNA; Species Specificity; sekvenční analýza DNA; Fishes; druhová specificita; molekulární sekvence - údaje; ryby; Phylogeny; Evolution, Molecular